Implementation and evaluation of automated tetrahedral–prismatic mesh generation software. (March 2016) - Eller, David; Tomac, Maximilian
Abstract: An open-source implementation of an efficient mesh generation procedure for hybrid prismatic–tetrahedral meshes intended for use in Reynolds-averaged Navier–Stokes solutions is presented. The method employed combines the established, and very fast, Delaunay-based tetrahedral mesh generatorTetGen with a novel technique for the creation of a prismatic layer, where constrained global optimization of the envelope is employed. Once a well-shaped envelope is thus obtained, a semi-structured layer of pentahedral elements is extruded between wall and envelope surface. Satisfactory mesh quality is demonstrated by comparing solutions obtained using the new meshes with reference data computed on high-quality advancing-front grids. Mesh generation time is shown to be substantially smaller than with many other methods. Overall, the presented implementation is deemed a valuable tool for cases where many meshes need to be generated for routine analyses and turnaround time is critical. This is an extended version of the paper presented at the 23rd International Meshing Roundtable in London, October 2014. Highlights: An open-source implementation for prismatic–tetrahedral mesh generation is presented. Global constrained optimization is employed to create prismatic layer envelope. We find that total mesh generation time is substantially reduced. Manual user intervention effort is smaller due to large degree of automation. Comparisons of RANS solutions demonstrate adequate mesh quality.